Economy and Social Commitment-Based Investment and Role of Board of Directors (BOD) toward Corporate Value - E, Indriani; R.P, Anton (International Journal of Engineering and Technology, 2019)
Economy and social commitment-based investment is a corporate investment policy strategy which can generate profits that are able to improve corporate values and meet the interests of stakeholders. Corporate social responsibility (CSR) activity is a high-cost program, but some companies consider that it does not give significant results to their corporate values. This study aims at bridging the gap between the study and practice of the CSR. It was conducted at go public companies in Indonesia from 2012-2014. The result of this study shows that the intensive role of the Board of Directors (BOD) strengthened the effect support of economy and social commitment-based investment to enhance the corporate values.Â Â